Karakteristik Kimia dan Sensori Selai Tamarillo (Solanum betaceum Cav.) Dengan Albedo Jeruk Pamelo (Citrus maxima L. Merr) - Arti Hastuti; Muhammad Fakih Kurniawan; Fairuz Irdina Ramadhanti; Siti Nurhalimah; Wilna Iznilillah (JURNAL AGROINDUSTRI HALAL, 2025)
Jam is a semi-wet food product made from fruits with added sugar. Tamarillo (Solanum betaceum Cav.) is a fruit whose processing is still limited, usually being made into juice. The aim of this study is to investigate and analyze the effects of the ratio between tamarillo pulp and pomelo albedo pulp on chemical characteristics (moisture content, crude fiber, total dissolved solids, and pH), sensory and hedonic properties, and to select the product for further antioxidant activity testing. The research design used is a Completely Randomized Design (CRD) with a single factor, which is the ratio of tamarillo pulp to pomelo albedo pulp, with four treatment levels: (100%:0%), (85%:15%), (70%:30%), and (55%:45%). The data were analyzed using ANOVA followed by Duncan's post hoc test at a 95% confidence level. The results showed that the jam product with the formulation of 85% tamarillo pulp and 15% pomelo albedo pulp significantly affected the chemical characteristics (moisture content 31.41%, pH value 3.96, IC50 antioxidant activity value of 8.73 ppm, classified as very strong, total dissolved solids value of 40.50%), with sensory and hedonic properties resulting in a jam product that had a reddish-purple color, a distinct tamarillo aroma, a sweet-sour taste, a non-bitter aftertaste, a soft texture in the mouth, easy spreadability, and an overall preference towards liking.